Decentralisation and the role of NGOs in combating corruption in the WASH sector - Bep van Oostrom; Cor Dietvorst (2006)
This paper questions the assumed relation between the decentralisation and privatisation of the provision of WASH services on the one hand and increased transparency and accountability on the other. Practices in India and Africa show that this is often not the case. Accountability and transparency are sometimes lost when the contractual arrangements between decentralised government and the private sector actors do not lead to involvement and informing user communities and when the role of local NGO’s is not recognised. As a result the quality of some work is poor, ownership of WASH services is low, and the equity principle is compromised. Nevertheless, these same decentralisation and privatisation processes create opportunities to empower communities and develop measures to combat private gain and increase transparency at the implementation level. In this paper some of these good practices are described. Particularly the role of the civil society in the promotion of accountability and honesty is crucial. NGO’s could play an important role.